Multiple Faces of Dynamin-related Protein 1 and Its Role in Alzheimer’s Disease Pathogenesis - Kandimalla, Ramesh (Biochim Biophys Acta, 2015)
Mitochondria play a large role in neuronal function by constantly providing energy, particularly at synapses. Recent studies suggest that amyloid beta (Aβ) and phosphorylated tau interact with the mitochondrial fission protein, dynamin-related protein 1 (Drp1), causing excessive fragmentation of mitochondria and leading to abnormal mitochondrial dynamics and synaptic degeneration in Alzheimer’s disease (AD) neurons. Recent research also revealed Aβ-induced and phosphorylated tau-induced changes in mitochondria, particularly affecting mitochondrial shape, size, distribution and axonal transport in AD neurons. These changes affect mitochondrial health and, in turn, could affect synaptic function and neuronal damage and ultimately leading to memory loss and cognitive impairment in patients with AD. This article highlights recent findings in the role of Drp1 in AD pathogenesis. This article also highlights Drp1 and its relationships to glycogen synthase kinase 3, cyclin-dependent kinase 5, p53, and microRNAs in AD pathogenesis.